Shale Reservoir 3D Structural Modeling Using Horizontal Well Data: Main Issues and an Improved Method - Shu, Zhiguo; Wang, Guochang; Luo, Yang; Wang, Chao; Chen, Yalin; Zou, Xianjun (Frontiers in Earth Science, 2021)
Shale oil and gas fields usually contain many horizontal wells. The key of 3D structural modeling for shale reservoirs is to effectively utilize all structure-associated data (e.g., formation tops) in these horizontal wells. The inclination angle of horizontal wells is usually large, especially in the lateral section. As a result, formation tops in a horizontal well are located at the distinct lateral positions, while formation tops in a vertical well usually are stacked in the same or similar lateral position. It becomes very challenging to estimate shale layer thickness and structural map of multiple formation surfaces using formation tops in horizontal wells. Meanwhile, the large inclination angle of horizontal wells indicates a complicated spatial relation with shale formation surfaces. The 3D structural modeling using horizontal well data is much more difficult than that using vertical well data. To overcome these new challenges in 3D structural modeling using horizontal well data, we developed a method for 3D structural modeling using horizontal well data. The main process included (1) adding pseudo vertical wells at formation tops to convert the uncoupled formation tops to coupled formation tops as in vertical wells, (2) estimating shale thickness by balancing the shale thickness and dip angle change of a key surface, and (3) detecting horizontal well segments landing in the wrong formations and adding pseudo vertical wells to fix them. We used our improved method to successfully construct two structural models of Longmaxi-Wufeng shale reservoirs at well pad scale and shale oil/gas field scale. Our research demonstrated that 3D structural modeling can be improved by maximizing the utilization of horizontal well data thus optimizing the quality of the structural model of shale reservoirs.